2018
DOI: 10.1371/journal.pone.0198327
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver index is a predictor of incident diabetes in patients with prediabetes: The PREDAPS study

Abstract: ObjectivesWe evaluated the ability of the Fatty Liver Index (FLI), a surrogate marker of hepatic steatosis, to predict the development of type 2 diabetes (T2D) at 3 years follow-up in a Spanish cohort with prediabetes from a prospective observational study in primary care (PREDAPS).MethodsFLI was calculated at baseline for 1,142 adult subjects with prediabetes attending primary care centers, and classified into three categories: FLI <30 (no steatosis), FLI 30–60 (intermediate) and FLI ≥60 (hepatic steatosis). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 75 publications
(83 reference statements)
4
38
0
1
Order By: Relevance
“…Our results show that individuals with isolated impaired HbA1c when diagnosed with pre-diabetes might have a slightly better cardiometabolic risk profile than those with isolated FPG, while those individuals with both impaired FPG and HbA1c had the worst cardiovascular risk. These results are in line with the findings of the prospective observational study in the primary care setting of a Spanish cohort with pre-diabetes (PREDAPS) of our group 35 36…”
Section: Discussionsupporting
confidence: 90%
“…Our results show that individuals with isolated impaired HbA1c when diagnosed with pre-diabetes might have a slightly better cardiometabolic risk profile than those with isolated FPG, while those individuals with both impaired FPG and HbA1c had the worst cardiovascular risk. These results are in line with the findings of the prospective observational study in the primary care setting of a Spanish cohort with pre-diabetes (PREDAPS) of our group 35 36…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes mellitus also has significant association with NAFLD 35 . Furthermore, a recent article has revealed that FLI is a predictor of diabetes mellitus in a longitudinal study 36 . In concordance, our data showed a stronger association between FLI and periodontitis prevalence in the subgroup with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IFG and IGT, the status of NAFLD associated with the newly categorized isolated high HbA1c group, which might have been categorized into the normal glycemic population in the past, had not been previously understood. Nevertheless, the prevalence of prediabetes with NAFLD has been estimated to range from 44 to 62% in the USA, from 45 to 78% in Germany and 60% in Korea, which suggests a future epidemic of liver complications 17 and the development of diabetes 18 . The disappearance of fatty liver could also be a prognostic factor for regression from IGT to normal glucose regulation in individuals with NAFLD 19 .…”
Section: Introductionmentioning
confidence: 99%